Hall detection of anisotropic domain walls during magnetic phase transition. (29th November 2017) - Chen, X Z; Liu, H; Yin, L F; Chen, H; Song, C; Pan, F
Abstract: We investigate the electrical detection of anisotropic antiferromagnetic/ferromagnetic (AFM/FM) domain walls in (2 at%) Pd-doped FeRh films. The Hall signals keep almost at zero at both AFM and FM states, while a sizeable Hall conductivity up to 300 (Ω cm) −1 emerges during the AFM–FM phase transition of Pd-doped FeRh films around room temperature. Such Hall signals could be ascribed to the transverse current scattered by the anisotropic AFM/FM domain walls, which are mainly aligned around the [1 0 0] axis of the Pd-doped FeRh films. The highly reproducible Hall signals in both the temperature and magnetic field-induced magnetic phase transition are supported by the observation of a nonrandom formation of AFM/FM domain walls. Our findings not only advance the understanding of the magnetic phase transitions, but also propose a considerable way for the detection of AFM/FM domain walls by an electrical means.